Crushing responses and energy absorption of bionic inspired corrugated honeycombs - Xu, Wenlong; Wang, Cheng; Liu, Baohua; Jia, Shiyu (International journal of impact engineering, 2023)
•Inspired by pomelo peel and bamboo structure, corrugated and layered honeycombs are designed and fabrication by metal 3D printing.•The deformation modes and energy absorption capacity of the bionic inspired honeycombs are experimentally investigated with quasi-static and dynamic drop-weight tests.•The influence of impact speed on the crashworthiness performance of the honeycombs is investigated. To improve the energy absorption of traditional structures, impact resistant natural materials are usually mimicked to develop novel structures with desirable energy absorption. In this work, inspired by the unique 3D corrugated microstructure of vascular bundles in pomelo peel, a new design of honeycomb structure with corrugated characteristics is proposed. Further, motivated by special nodal bulkhead architecture of bamboo, layered honeycombs with diaphragms are designed and fabrication by metal 3D printing technology. The quasi-static and dynamic crushing responses and energy absorption characteristics of six types of bio-inspirational honeycombs (ISWH, LSWH, ISCH, LSCH, IPCH and LPCH) are studied using quasi-static testing machine and dynamic drop-weight impact experimental systems. To investigate the effect of impact speed on the crashworthiness performance of the honeycombs, the tests of the honeycombs impacted by the drop-weight with two different mass (106.07 and 59.60 Kg) and three impact velocity (V1=6.23, V2=8.82 and V3=11.77 m/s), respectively, are performed. The experimental results indicate that the crush failure mode of the layered honeycombs is more regular than that of the integrated honeycombs. Failure of all layered honeycombs occurs first at the junction of the honeycomb and diaphragms. Under impact loading, the layered corrugated wall honeycombs exhibit a greater final crushing distance than their corresponding integrated honeycombs. The design of corrugated wall can effectively reduce the initial peak force of the integrated honeycombs, while the layered honeycomb design also facilitates the reduction of the initial peak force, thus avoiding damage to personnel or equipment from excessive peak collision forces. The layered design will reduce the specific energy absorption of the integrated honeycombs in most cases, but a reasonable combination of layered and corrugated wall design can also effectively increase the specific energy absorption of the honeycombs under a specific loading speed. And, the layered design can also effectively improve the crush force efficiency of the corresponding integrated honeycombs.